The Prevalence of Mental Problems for Chinese Children and Adolescents During COVID-19 in China: A Systematic Review and Meta-Analysis - Chai, Jiabao; Xu, Huili; An, Ning; Zhang, Pan; Liu, Fuquan; He, Sushuang; Hu, Na; Xiao, Xue; Cui, Yonghua; Li, Ying (Frontiers in Pediatrics, 2021)
The outbreak of coronavirus disease 2019(COVID-19) has caused mental problems among the public and medical staff in China, especially for children and adolescents, a vulnerable group that might present with more mental problems. It seems that there is a rapid growth in the mental problems (such as depression problem or anxiety problem) of Chinese children and adolescents during the outbreak of COVID-19. Although several studies reported the prevalence of depression or anxiety problems for children and adolescents, the results are different across different age groups and sex groups. Moreover, the sample size of these studies was small. In the present study, we aim to perform a meta-analysis to identify the confirmed prevalence of depression and anxiety problems for Chinese children and adolescents during home confinement. There are six databases were searched including PubMed, Web of Science, PsycINFO, Google Scholar and the China National Knowledge Infrastructure(CNKI), WanFang Date，both the inclusion and exclusion criteria were developed. Finally, a total of 12 studies were included in this meta-analysis. The protocol of this systematic review was registered with INPLASY (protocol ID: INPLASY202150032). It found that the pooled prevalence of mental problems was 28% (95% confidence interval, CI: 0.22 to 0.34), and the depression and anxiety problem for children and adolescents in China was 22% (95% CI: 0.16 to 0.30) and 25% (95% CI: 0.20 to 0.32) based on a random effect model, separately. Subgroup analysis was used to identify that there are no differences between different age groups (primary and middle school vs. high school)(p = 0.26). Meta-regression analysis was performed and the results showed that the moderator of boy percentage was a significant factor (p = 0.04). It indicated that there was an increasing number of children and adolescents with mental problems during the home confinement. It suggested that we should pay more attention to this vulnerable population during a public health crisis in future, especially for the girl's groups, and more detailed implements for mental health management were needed and should be prepared.